DNAzyme Delivery Approaches in Biological Settings - W.S. Chan, Cecilia; M. Khachigian, Levon (Current Medicinal Chemistry, 2013)
DNAzymes are DNA-based catalytic molecules that have potential use in a range of disorders where the targeted gene plays an important role in disease pathogenesis. DNAzymes are at a comparatively early developmental stage as alternatives to conventional therapies. The biological action of DNAzymes on target mRNA requires efficient delivery into target cells and this hurdle has hampered their broader use, particularly in systemic settings. DNAzymes have been delivered in naked form without a carrier or combined with agents such as polymers and liposomes. This article reviews these and other delivery approaches and offers perspectives on future methodologies for improved DNAzyme delivery and utility as novel drugs.
Keywords: catalytic